2012
DOI: 10.1111/j.1746-1561.2012.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a Diabetes Education Curriculum for School Personnel on Disease Knowledge and Confidence in Caring for Students

Abstract: BACKGROUND: School personnel may lack knowledge of diabetes and be unprepared to address the needs of students with type 1 diabetes. This project evaluated the effectiveness of a type 1 diabetes education program for school personnel on increasing knowledge of diabetes and confidence in caring for students with diabetes. METHODS: Two types of diabetes education programs were created for school personnel. The basic program provided a 60‐minute overview of diabetes. The expanded program, intended for volunteer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 23 publications
2
35
0
5
Order By: Relevance
“…The findings of this analysis are in accordance with other studies examining similar education programs related to diabetes management in that they all demonstrated an increase in knowledge, confidence, and ability of attendees to effectively provide care to students with diabetes (Bachman & Hsueh, 2008;Bobo, Kaup, McCarty, & Carlson, 2011;Smith et al, 2012). Bachman and Hsueh (2008) concluded that it is necessary for school nurses to have the opportunity to receive updated information on diabetes management for children through CE.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this analysis are in accordance with other studies examining similar education programs related to diabetes management in that they all demonstrated an increase in knowledge, confidence, and ability of attendees to effectively provide care to students with diabetes (Bachman & Hsueh, 2008;Bobo, Kaup, McCarty, & Carlson, 2011;Smith et al, 2012). Bachman and Hsueh (2008) concluded that it is necessary for school nurses to have the opportunity to receive updated information on diabetes management for children through CE.…”
Section: Discussionsupporting
confidence: 89%
“…Lectures and educational flyers are strategies to inform and guide the school staff decision‐making process while facing difficulties and emergencies, lowering the typical stress to these situations . Consequently, increased confidence in the school staff's to care for T1DM children is observed . National and international organizations have made educational T1DM booklets available to inform school staffs.…”
Section: Discussionmentioning
confidence: 99%
“…, Smith et al . ). These findings are based on the delivery of education programmes to small samples of participants and do not include control groups.…”
Section: Key Barriers and Facilitatorsmentioning
confidence: 97%